Investigating the use of social media in intimate social relationships. Issue 4 (12th March 2023) - Sutcliffe, Alistair; Dunbar, Robin; El-Jarn, Hatana
ABSTRACT: Research Question: Is social media activity related to layers of intimacy in social relationships? Study design: Mixed methods, survey on social relationships with 30 participants who identified up to 20 best/close friends and their use of social media. The same 30 participants were interviewed to gather details of how they communicated with close and best friends, and how they used social media/CMC to maintain their social relationships. Analysis: communication frequency, content and rationale were classified according to the intimacy of relationships between the ego and recipients as best or close friends. Results: Communication with best friends was either face to face or by conversational media (phone, text) in both normal use and emergencies. Emotional support and intimate topics dominated these exchanges. Communication with close friends used broadcast social media (Facebook), text and phone. Face to Face (FtF), phone and text were preferred by the majority of participants for social relationship maintenance. Implications: Dyadic (person to person) communication face to face and via social media, phone and text are vital to provide social and emotional support in intimate social relationships. Social media in particular Facebook broadcast functions play a role in supporting awareness of both intimate and less intimate social relationships.